2021
DOI: 10.1073/pnas.2100978118
|View full text |Cite
|
Sign up to set email alerts
|

Solar anti-icing surface with enhanced condensate self-removing at extreme environmental conditions

Abstract: The inhibition of condensation freezing under extreme conditions (i.e., ultra-low temperature and high humidity) remains a daunting challenge in the field of anti-icing. As water vapor easily condensates or desublimates and melted water refreezes instantly, these cause significant performance decrease of most anti-icing surfaces at such extreme conditions. Herein, inspired by wheat leaves, an effective condensate self-removing solar anti-icing/frosting surface (CR-SAS) is fabricated using ultrafast pulsed lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…Dash et al developed a scalable photo-thermal trap exhibiting efficient solar deicing performance . Zhang et al fabricated a film with efficient solar anti-icing and enhanced condensate self-removing effects …”
Section: Introductionmentioning
confidence: 99%
“…Dash et al developed a scalable photo-thermal trap exhibiting efficient solar deicing performance . Zhang et al fabricated a film with efficient solar anti-icing and enhanced condensate self-removing effects …”
Section: Introductionmentioning
confidence: 99%
“…Compared with electro‐thermal heat techniques, solar energy as the renewable source is free and sustainable from nature. Recently, researchers investigated sun light (or artifical light) to replace electric power, and developed photo‐thermal promoted AIM by combining passive AIM (i.e., SHSs, [ 106 ] lubricating surfaces, [ 107–110 ] and other icephobic surfaces [ 111,112 ] ) ( Figure ) with active photo‐thermal heating with the help of various absorbers (i.e., Fe 3 O 4 , [ 107,108,113–115 ] candle soot, [ 12,116 ] carbon nanotubes (CNTs), [ 89,90,112,117–126 ] carbon nanofibers, [ 111 ] CNTs/Fe 3 O 4 @poly(cyclotriphosphazene‐co‐4,4′‐sulfonyldiphenol) (PZS), [ 127 ] cermet, [ 32 ] I 2 , [ 128 ] SiC, [ 129 ] polypyrrole (PPy), [ 98 ] melanin, [ 130 ] CNTs/SiO 2 , [ 131 ] Fe/candle soot, [ 106 ] Fe/Cu, [ 132 ] titanium nitride (TiN), [ 133,134 ] Ti 2 O 3 , [ 135 ] Au/TiO 2 , [ 66,136 ] Au/SiO 2 , [ 137 ] reduced graphene oxide (rGO), [ 138 ] graphite, [ 139 ] SiO 2 /CuFeMnO 4 , [ 140 ] MXene, [ 141 ] and black engineered aluminum [ 142,143 ] ) (See Table 3 ). Generally, the absorption capacity of these absorbers differs from one to another, and the photo‐thermal effect usually occurs under different light wavelengths, such as solar radiation, [ 107 ] near infrared irradiation, [ 89,108,118,129 ] and infrared irradiation (See Table 3).…”
Section: Photo‐thermal Promoted Aimmentioning
confidence: 99%
“…fabricated an effective solar anti‐icing surface with superhydrophobicity, and this photo‐thermal SHS (fraction of dry area is 72%) can reach 5.5 °C within 1400 s under 1 sun illumination with an ambient temperature of −50 °C. [ 132 ] Interestingly, they found that a certain fraction of dry area is necessary for the rational design of photo‐thermal promoted AIM to remain unfrozen under a specific environmental condition (i.e., −50 °C under 1 sun). [ 132 ] Zhang et al.…”
Section: Photo‐thermal Promoted Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] In addition, other photo‐active materials were hybridized to achieve a complementary or synergetic photothermal effect. [ 4 ] Very recently, taking advantage of ultrafast pulsed laser deposition technology, Zhang and coworkers [ 5 ] fabricated hierarchically structured iron oxides with ultralow reflectance and high light‐to‐heat conversion. The rational design of surface morphologies opens an avenue for high light‐harvesting, which has also been demonstrated on forest‐like graphene film.…”
Section: Introductionmentioning
confidence: 99%